Pengaruh Media Pembelajaran Audio Visual terhadap Hasil Belajar Siswa pada Mata Pelajaran TIK - Putri Anisa Meilanda; Duri Duri; Merry Trianjani; Yuniarti Juanti; Ramadiansyah Ramadiansyah (Departement of Mathematics Education, 2023)
This research is an experimental research using quasi-experimental methods. The research was conducted at SMP 13 Pontianak with class VIII B as the sample. This study aimed to see the effect of audio-visual learning media on student learning outcomes in ICT subjects. The research was conducted in two meetings. In the first meeting, learning was carried out without using audio-visual media. And the second meeting carried out learning using audio-visual media. The results of student learning show that the average value of student learning outcomes without using audio-visual media is 54.15 while the average value of student learning outcomes using audio-visual media is 73.23. These results indicate that learning using audio visual obtains a higher score than without audio visual media. From the calculation of the T test, it was obtained that T count 8.9771212 > T table 1.6772242 Ho was rejected with the conclusion that there was an influence by using audio-visual media on student learning outcomes.